A method for producing high compacted density iron phosphate
Patent Information
- Application Number
- CN202411210651.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-08-30
AI Technical Summary
In the existing technology, iron phosphate crystals are prone to encapsulating sulfates in the reaction solution during growth, resulting in decreased product purity and low compaction density.
By controlling the excess iron and adjusting the pH of the monoammonium phosphate solution, the oxidation reaction generates Fe3H6(PO4)43+ ions, which form flocculent complexes with sulfate ions, thus preventing sulfate ions from being trapped in the crystals. At the same time, a two-step aging process is used to control crystal growth, resulting in a mixed form of iron phosphate consisting of large and small particles.
The purity and compaction density of ferric phosphate were improved, the sulfur content in the product was reduced, and the compaction density reached 2.53 g/cm3, which is far higher than that of existing technologies.
Smart Images

Figure CN119079957B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of ferric phosphate production technology, specifically a method for producing high-pressure, high-density ferric phosphate. Background Technology
[0002] Iron phosphate, with the chemical formula FePO4, is an inorganic compound and an important precursor for lithium iron phosphate (LFP), the cathode material of lithium-ion batteries. In recent years, lithium-ion batteries, as a new generation of green batteries, have attracted widespread attention due to their advantages such as high theoretical capacity, high voltage, low self-discharge rate, excellent cycle performance, wide operating temperature range, and environmental friendliness. With the continuous expansion of new energy vehicles and energy storage, the demand for lithium-ion batteries is also growing rapidly. As a crucial precursor for the synthesis of LFP, the preparation process and product quality of iron phosphate directly affect the performance, quality, and cost of LFP cathode materials. Obtaining stable, uniform, and low-cost iron phosphate is a hot topic of great concern in the lithium battery industry.
[0003] In existing technologies, the main production process for iron phosphate is the liquid-phase precipitation method. This method primarily uses ferric sulfate and phosphate as raw materials, undergoing an oxidation reaction in an aqueous solution. After oxidation, the product is aged, filtered, dried, and calcined to produce iron phosphate. During the oxidation reaction to produce iron phosphate, the product undergoes two stages: nucleation and crystal growth. The initial stage is the iron phosphate nucleation stage, forming numerous small iron phosphate nuclei with high purity. However, as the nuclei grow, they tend to encapsulate sulfate ions in the reaction solution, forming a mixture of FePO4·xMSO4. Therefore, during the crystal growth stage, the crystal size and sulfur content of iron phosphate increase synchronously. The encapsulated sulfate affects the purity of the iron phosphate product, thus impacting the performance of the prepared lithium iron phosphate battery. Summary of the Invention
[0004] The purpose of this invention is to provide a method for producing high-density ferric phosphate, which solves the technical problem mentioned above in the prior art where ferric phosphate crystals easily encapsulate sulfates in the reaction solution during the growth process, resulting in impurities in the final ferric phosphate product.
[0005] To solve the above problems, the technical solution adopted by the present invention is as follows: A method for preparing high-pressure solid density ferric phosphate, comprising the following steps:
[0006] S1: Preparation of ferrous sulfate solution: After mixing titanium dioxide residue with demineralized water, add phosphoric acid, ammonia and flocculant to pretreat the solution. After complete dissolution, filter to remove suspended insoluble matter, and obtain FeSO4·7H2O solution after vacuum filtration.
[0007] S2: Solution preparation, oxidation, and reaction: Calculate the required amount of phosphoric acid while ensuring an iron excess of 8%-12%. Prepare a monoammonium phosphate solution by mixing phosphoric acid and ammonia water, and control the pH of the monoammonium phosphate solution to 6.5-7.5. Mix the monoammonium phosphate solution with the FeSO4·7H2O solution prepared in S1. After mixing, slowly add hydrogen peroxide to the mixture to carry out the oxidation reaction. Finally, control the pH of the reaction between 2 and 3.
[0008] S3: Washing and filtration: Add demineralized water to the filter cake after vacuum filtration of the mixture at a material-to-water ratio of 1:3, and repeat the washing and filtration process three times to obtain ferric phosphate.
[0009] The beneficial effects of this implementation plan are as follows:
[0010] 1. In the existing oxidative synthesis of ferric phosphate, after the ferric phosphate crystals enter the crystal growth stage, the crystal nuclei tend to encapsulate sulfate ions in the reaction solution, forming a mixture of FePO4·xMSO4. Therefore, during the crystal growth stage, the crystal size of ferric phosphate and the sulfur content in the crystals increase synchronously. The encapsulated sulfates affect the purity of the ferric phosphate product. In this application, the iron content is increased in excess, and the pH value of monoammonium phosphate is controlled, so that during the reaction, the oxidized Fe... 3+ The ions do not directly react with phosphate ions to form FePO4, but instead first undergo a coordination reaction to form Fe3H6(PO4)4. 3+ Ion, Fe3H6(PO4)4 3+ and SO4 2+ The formation of flocculent complexes prevents SO4 from being trapped during the formation of ferric phosphate. 2+ The reaction equation is as follows: First reaction: 3Fe 3+ +4H3PO4=Fe3H6(PO4)4 3+ +6H + The second reaction: Fe3H6(PO4)4 3+ +6H₂O=3FePO₄*2H₂O+H₃PO₄+3H + The reaction process is as follows: Initially, due to the relatively high pH value of monoammonium phosphate, the pH value of the mixed solution of ferrous iron and monoammonium phosphate is also relatively high. After adding hydrogen peroxide, the first reaction proceeds in the forward direction, producing Fe3H6(PO4)4. 3+ and SO4 2+ H is generated during the formation of the complex. + The pH of the mixture decreased, providing a suitable pH environment for the formation of ferric phosphate. This reduced the pH of most of the other Fe in the reaction solution. 3+ Iron phosphate can then be produced normally, with the reaction formula being: 2FeSO4 + H2PO4 4- +H₂O₂→FePO₄↓+2SO₄ 2-+H2O; As hydrogen peroxide continues to increase, a large amount of Fe3H6(PO4)4 is generated. 3+ Simultaneously, the pH decreases further during the formation of Fe3H6(PO4)4 3+ The resulting reaction is either inhibited or proceeds in reverse, and due to Fe3H6(PO4)4 3+ If the concentration is too high, the second reaction proceeds further in the forward direction to generate ferric phosphate, which releases sulfate ions. At this point, since most of the ferric phosphate has already completed crystal growth, the effect of sulfate ions is minimal. Therefore, the ferric phosphate in this application has a relatively high purity.
[0011] 2. In existing technologies, the synthesis of ferric phosphate is a one-step reaction, resulting in uniformly sized crystals. This makes it difficult to fill the gaps between the particles during compression. In contrast, the ferric phosphate in this application is generated in two parts: Fe2(SO4)3 + 2NH4H2PO4 = 2FePO4 + (NH4)2SO4 + 2H2SO4, and Fe3H6(PO4)4. 3+ +6H₂O=3FePO₄*2H₂O+H₃PO₄+3H + The ferric phosphate produced in the first reaction is slow and has no sulfate interference, so it slowly grows into large particles and forms cubic ferric phosphate dihydrate after aging. The other part of the ferric phosphate produced in the second reaction precipitates from the complex ions and adsorbs on the surface of the large ferric phosphate produced in the first reaction. After aging, it forms amorphous fine particles. When compacted, the force of the fine particles fills the gaps in the cubic crystals. Therefore, its compaction density is higher than that of the flaky or cubic ferric phosphate in the prior art.
[0012] Further, S4: Segmented aging: Add demineralized water to the filter cake after S3 filtration at a ratio of 1:2 (material to water), stir evenly, raise the solution temperature to 55-65℃, add ammonia water to the solution, control the pH value of the reaction solution between 1.8 and 2.4, keep warm for 1-2 hours for the first stage of aging, raise the temperature to 90-100℃, add phosphoric acid, keep warm for 3-4 hours for the second stage of aging, and precipitate FePO4·2H2O; S5: Filtration, washing, drying and calcination: After aging, filter the solution and add demineralized water at a ratio of 1:2 (material to water) for washing, then filter and dry, and calcinate the dried sample to obtain the iron phosphate product.
[0013] Furthermore, the iron-to-phosphorus ratio in S2 is 1.1:1.
[0014] Furthermore, the pH value of monoammonium phosphate in S2 is controlled at 7, and the pH of the final reaction is controlled between 2.2 and 2.3.
[0015] Furthermore, in S4, the first stage aging temperature is controlled at 60℃, the pH value is controlled at 2.2-2.3, and the heat preservation time is controlled at 1 hour.
[0016] Furthermore, in S4, the second stage aging temperature is controlled at 95°C, and the heat preservation time is controlled at 3 hours. Attached Figure Description
[0017] Figure 1 This is a SEM image of the iron phosphate product from Example 1 of the present invention. Detailed Implementation
[0018] The following detailed description illustrates the specific implementation method:
[0019] First, it should be understood that, when used in this specification and the appended claims, the terms "comprising" and "including" indicate the presence of the described features, integrals, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integrals, steps, operations, elements, components and / or collections thereof.
[0020] It should also be understood that the terminology used in this specification is for the purpose of describing particular embodiments only and is not intended to limit the invention. As used in this specification and the appended claims, the singular forms “a,” “an,” and “the” are intended to include the plural forms unless the context clearly indicates otherwise.
[0021] It should also be further understood that the term "and / or" as used in this specification and the appended claims refers to any combination of one or more of the associated listed items and all possible combinations, and includes such combinations.
[0022] Example 1
[0023] S1: Prepare ferrous sulfate solution
[0024] After mixing titanium dioxide residue with demineralized water (titanium dioxide residue refers to the solid byproduct of ferrous sulfate in the sulfuric acid process for producing titanium dioxide), 1.5-2.5 times the mass of titanium dioxide residue is added to the demineralized water to dissolve it. Ammonium phosphate is added to adjust the pH to 2-3, ensuring that the ferrous sulfate in the titanium dioxide residue dissolves in the water. After stirring and dissolving for 1-2 hours, a flocculant is added to pretreat the undissolved impurities in the solution. The flocculant flocculates small particles of impurities into suspended insoluble impurity clusters. After complete dissolution, the suspended insoluble matter is removed by filtration. After vacuum filtration, a FeSO4·7H2O solution is obtained, with the concentration of the FeSO4·7H2O solution controlled at 4%-6%.
[0025] S2: Solution oxidation and reaction
[0026] The required amount of phosphoric acid was calculated based on an iron-to-phosphorus ratio of 1.1:1. Ammonia was added to the required amount of phosphoric acid to react with the ammonia to form a monoammonium phosphate solution. The pH was then adjusted to 7 using ammonia. After the monoammonium phosphate solution was prepared, it was directly mixed with FeSO4·7H2O solution. Since no oxidant was added, the reaction did not proceed. After the monoammonium phosphate and FeSO4·7H2O solution were thoroughly mixed, the pH of the resulting mixture was high (approximately 4.0), due to the pH of the monoammonium phosphate solution being 7. At this point, hydrogen peroxide was slowly added dropwise to the mixture to oxidize ferrous iron to ferric iron. However, because there was no pH environment conducive to the formation of ferric phosphate, ferric phosphate was not directly formed at this stage; instead, a reaction of 3Fe3+ and ferric iron was observed. 3+ +4H3PO4=Fe3H6(PO4)4 3+ +6H + The coordination reaction produces Fe3H6(PO4)4 3+ and H + H + This causes the pH of the mixture to decrease, creating a pH environment conducive to the formation of ferric phosphate, which then allows most of the Fe3+ to be generated. + The normal reaction produces ferric phosphate, while the SO4 produced by the reaction... 2+ With Fe3H6(PO4)4 3+ The formation of flocculent complexes does not affect the growth of ferric phosphate crystals. With continued addition of hydrogen peroxide, the pH further decreases, and Fe3H6(PO4)4... 3+ As the concentration of Fe increases, Fe3H6(PO4)4 is generated. 3+ The reaction is either inhibited or reversed, hydrolyzing to produce ferric phosphate. At this point, sulfate ions are released. Since most of the ferric phosphate has already completed crystal growth, the effect of sulfate ions is minimal. The final pH of the reaction is controlled between 2.2 and 2.3.
[0027] Furthermore, at the beginning of the reaction, the pH value was too high, allowing iron to react and form Fe3H6(PO4)4. 3+ While forming a complex with sulfate ions, it can also additionally form ferric hydroxide colloids to form flocculent substances with sulfates. This ensures that the ferric phosphate in this invention does not encapsulate sulfate ions during crystal growth, resulting in high purity and Fe... 3+ The normal reaction produces ferric phosphate, Fe3H6(PO4)4 3+ Hydrolysis produces ferric phosphate, which forms two forms of ferric phosphate, Fe. 3+ The normal reaction produces ferric phosphate. Due to the growth time of its crystals, it precipitates as large, amorphous ferric phosphate blocks. After aging, it becomes large cubes, Fe3H6(PO4)4 3+The ferric phosphate produced by hydrolysis is fine and amorphous, and it also becomes small particles after aging. Therefore, when the ferric phosphate of this application is compressed, the fine particles will fill the gaps in the cubic crystals under stress, so its compaction density is higher than that of the flaky or cubic ferric phosphate in the prior art.
[0028] After hydrogen peroxide is added, stir and react for 2-3 hours to obtain a mixture of ferric phosphate products.
[0029] S3: Washing and Filtering
[0030] After the mixture of ferric phosphate products is filtered, the filter cake is washed with desalinated water at a weight ratio of 1:3 (material to water). The washing is repeated three times. Washing can effectively reduce the metal impurities and sulfur content in the ferric phosphate filter cake. After washing, ferric phosphate filter cake is obtained.
[0031] S4: Aging
[0032] The washed ferric phosphate filter cake was added to desalinated water at a weight ratio of 1:2 (material to water). After stirring evenly, the solution temperature was raised to 60°C and kept warm. At the same time, ammonia water was added to the slurry to raise the pH value to between 2.2 and 2.3, and the mixture was kept warm and aged for 1 hour.
[0033] The aging process aims to rapidly dissipate the moisture in amorphous ferric phosphate and form a stable crystal structure. Therefore, it typically requires a high temperature of around 90°C to accelerate the redistribution of moisture within the amorphous ferric phosphate and form stable dihydrate ferric phosphate crystals. However, this application uses a relatively low temperature (60±5°C) environment for initial aging for 1 hour. The main reason for this is that at lower temperatures, the supersaturation of ferric phosphate is greater, the moisture dissipation process of amorphous ferric phosphate crystals is slower, and small amorphous crystal particles tend to agglomerate between larger particles, resulting in a more uniform distribution between small and large particles. Furthermore, during the aging process, the pH of the slurry continuously decreases, and the H... + As the concentration gradually increases, the H in the solution + It can inhibit the formation of precipitate in solution, and ferric phosphate particles cannot fully aggregate. Therefore, adding ammonia water neutralizes H+. + The inhibitory effect was reduced, and iron phosphate crystals gained more opportunities for growth and development. Subsequently, the temperature was raised to 95℃ and held for 3 hours. Phosphoric acid was added, at a rate of 1% to 3% of the liquid level (volume) of the aging material, to adjust the acid-base environment for aging. After the temperature was increased, H... + The inhibitory effect of PO4 is no longer obvious, while PO4 3-The increase of promotes the transformation of disordered amorphous precipitates into stable binary phases. Ferric phosphate reduces internal energy, and high temperature can effectively increase the rate of water dissipation in amorphous ferric phosphate, thereby increasing the transformation of ferric phosphate from the amorphous state of FePO4·xH2O to the binary crystallization of FePO4·2H2O, thus improving the crystallinity of ferric phosphate.
[0034] S5: Filtration, washing, drying, and calcination
[0035] After filtration, the aged solution is washed with deionized water at a ratio of 1:2. After filtration again, the filter cake is dried in an oven at 160℃ for 2 hours. The dried sample is then calcined in a muffle furnace at 650℃ for 2 hours to obtain the ferric phosphate product. The SEM image of the final ferric phosphate product is shown below. Figure 1 As shown, its crystals consist of large, blocky particles and small, amorphous particles, and it has a high compaction density.
[0036] Its relevant performance data are as follows: Unless otherwise specified, all metal ion values are in mg / kg.
[0037]
[0038] The above data shows that the compacted density of the iron phosphate product in this application is 2.53 g / cm³. 3 It is far higher than the market average of 2.15g / cm³. 3 The sulfur content of the iron phosphate product is only 65 mg / kg, which is much lower than that of other iron phosphate products prepared from titanium dioxide slag, and other metal impurities are at a low level.
[0039] Example 2
[0040] The difference between Example 2 and Example 1 is that in Example 2, the iron-to-phosphorus ratio in S2 (solution oxidation and reaction) is 1.08:1; the pH of monoammonium phosphate is controlled at 6.5, and the final reaction pH is controlled between 2.4 and 2.7; and in S4 (aging), the low-temperature aging temperature is 55℃, and ammonia water is added to the slurry to raise the pH to between 2.0 and 2.2, followed by aging at this temperature for 1.5 hours, and the high-temperature aging temperature is 90℃ for 3.5 hours. The rest of the process is exactly the same as in Example 1.
[0041] The relevant performance data for Example 2 are as follows: Unless otherwise specified, all metal ion values are in mg / kg.
[0042]
[0043] Example 3
[0044] The difference between Example 3 and Example 1 is as follows: In Example 3, S2: the iron-to-phosphorus ratio in the solution preparation, oxidation, and reaction is 1.12:1; the pH of monoammonium phosphate is controlled at 7.5, and the final reaction pH is controlled between 2.7 and 3.0; and in S4: the low-temperature aging temperature is 65℃, and ammonia water is added to the slurry to raise the pH to between 1.8 and 2.0, followed by aging at this temperature for 2 hours, and the high-temperature aging temperature is 100℃ for 3 hours. The rest of the process is exactly the same as in Example 1.
[0045] The relevant experimental data for Example 3 are as follows: Unless otherwise specified, all metal ion values are in mg / kg.
[0046]
[0047] Comparative Example 1
[0048] Comparative Example 1 prepared ferric phosphate by the following steps:
[0049] (1) Dissolution and purification of ferrous sulfate: The solid byproduct of ferrous sulfate produced by the sulfuric acid process for titanium dioxide production is dissolved in water and iron powder is added. The filtrate is collected to obtain a purified ferrous sulfate solution.
[0050] (2) Oxidation of ferrous sulfate: Add hydrogen peroxide to the refined ferrous sulfate solution and react fully. The molar ratio of H2O2 in the added hydrogen peroxide to iron in the refined ferrous sulfate solution is 0.7:1. The reaction temperature is 45℃ and the reaction time is 30 min to obtain an oxidized solution.
[0051] (3) Preparation of iron phosphate: Add a 25% (w / w) monoammonium phosphate solution to the oxidation solution. The molar ratio of NH4H2PO4 in the added monoammonium phosphate solution to iron in the oxidation solution is 1:1. Add the monoammonium phosphate solution at a uniform rate and simultaneously heat the reaction with steam at a temperature of 80-90℃. The addition time of the monoammonium phosphate solution is 90 min, and the total reaction time is 2.5 h to obtain iron phosphate slurry.
[0052] (4) Primary filtration and pulping: The ferric phosphate slurry is subjected to primary filtration, the solid part is collected and washed, and the washing endpoint is that the conductivity of the effluent is ≤4000μs / cm to obtain the primary filter cake; pure water is added to the washed primary filter cake and stirred, and then transferred to the conversion kettle for aging to obtain the aged ferric phosphate slurry.
[0053] (5) Multi-stage filtration: The aged ferric phosphate slurry is subjected to secondary filtration, the solid part is collected and washed, and the washing endpoint is the effluent conductivity ≤1500μs / cm to obtain a secondary filter cake; pure water is added to the washed secondary filter cake and stirred, and then tertiary filtration is performed to collect the solid part to obtain a tertiary filter cake.
[0054] (6) Drying-calcining-pulverizing: The three-stage filter cake is dried to obtain ferric phosphate containing crystal water. The ferric phosphate containing crystal water is calcined in a rotary kiln at a temperature of 600℃ for 2.5h. After calcination, it is sent to a pulverizing device for pulverization. The exhaust gas after pulverization is discharged at high altitude after passing through a pulse dust collector. The pulverized material is mixed evenly to obtain high-pressure compacted ferric phosphate.
[0055] The compacted density of the ferric phosphate prepared in Comparative Example 1 was 0.93 g / cm³.
[0056] Compared with the comparative example, the compaction density of the iron phosphate product of this application is much higher than that of the prior art.
[0057] The above descriptions are merely embodiments of the present invention, and common knowledge regarding specific structures and characteristics is not elaborated upon here. It should be noted that those skilled in the art can make various modifications and improvements without departing from the structure of the present invention, and these should also be considered within the scope of protection of the present invention. These modifications and improvements will not affect the effectiveness of the present invention or the practicality of the patent. The scope of protection claimed in this application should be determined by the content of its claims, and the specific embodiments described in the specification can be used to interpret the content of the claims.
Claims
1. A method for preparing high-density iron phosphate, characterized in that: Includes the following steps: S1: Preparation of ferrous sulfate solution: After mixing titanium dioxide residue with demineralized water, add phosphoric acid, ammonia and flocculant to pretreat the solution. After complete dissolution, filter to remove suspended insoluble matter, and obtain FeSO4·7H2O solution after vacuum filtration. S2: Solution preparation, oxidation, and reaction: Calculate the required amount of phosphoric acid while ensuring an 8%-12% iron excess. Prepare a monoammonium phosphate solution by mixing phosphoric acid and ammonia, and control the pH of the monoammonium phosphate solution to 6.5-7.
5. Mix the monoammonium phosphate solution with the FeSO4·7H2O solution prepared in S1. After mixing, slowly add hydrogen peroxide to the mixture to carry out the oxidation reaction. Finally, control the pH of the reaction between 2 and 3. S3: Washing and filtration: Add demineralized water to the filter cake after vacuum filtration of the mixture at a material-to-water ratio of 1:3, and repeat the washing and filtration process three times to obtain ferric phosphate.
2. The method for preparing high-density ferric phosphate according to claim 1, characterized in that: It also includes the following steps: S4: Segmented aging: Add demineralized water to the filter cake after S3 filtration at a ratio of 1:2 (material to water). After stirring evenly, raise the solution temperature to 55-65℃, add ammonia water to the solution, control the pH value of the reaction solution between 1.8 and 2.4, and keep it at this temperature for 1-2 hours for the first stage of aging. Raise the temperature to 90-100℃, add phosphoric acid, and keep it at this temperature for 3-4 hours for the second stage of aging. The precipitate is FePO4·2H2O. S5: Filtration, washing, drying and calcination: After filtration, the aged solution is washed with desalinated water at a ratio of 1:
2. After washing, it is filtered and dried. The dried sample is then calcined to obtain the iron phosphate product.
3. The method for preparing high-density ferric phosphate according to claim 2, characterized in that: The iron-to-phosphorus ratio in S2 is 1.1:
1.
4. The method for preparing high-density ferric phosphate according to claim 3, characterized in that: The pH value of monoammonium phosphate in S2 is controlled at 7, and the pH of the final reaction is controlled between 2.2 and 2.
3.
5. The method for preparing high-density ferric phosphate according to claim 4, characterized in that: In the S4 process, the first stage aging temperature is controlled at 60℃, the pH value is controlled at 2.2-2.3, and the holding time is controlled at 1 hour.
6. The method for preparing high-density ferric phosphate according to claim 5, characterized in that: The second stage aging temperature in S4 is controlled at 95℃, and the holding time is controlled at 3 hours.
Citation Information
Patent Citations
Synthesizing method for low-cost battery-grade iron phosphate
CN106044735A
Efficient preparation method of battery-grade iron phosphate
CN114988383A
